2018
DOI: 10.1097/der.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Atopic Dermatitis and Pattern of Drug Therapy in Malaysian Children

Abstract: The overall prevalence is comparable to that reported in the International Study of Asthma and Allergies in Childhood Phase One. There is an association between ethnicity and AD prevalence. Topical corticosteroids and emollients are the mainstay of AD management among Malaysians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 2 publications
1
16
0
1
Order By: Relevance
“…Children in Singapore have an AD prevalence of 20.6%, nearly twice that of Singaporean adults (11.1%) [4]. In Malaysia, the overall prevalence of childhood AD is 13.4%, and it is most common in Malays, males, children aged \ 2 years, and those with an atopic background, such as asthma, hay fever, and family history of atopic diseases [5]. A study using Korean national statistics gathered from health insurance data reported that the prevalence of AD in 2008 ranged from 26.5% in 12-to 23-month-old infants to 2.4% in 18 year olds [6].…”
Section: Introductionmentioning
confidence: 99%
“…Children in Singapore have an AD prevalence of 20.6%, nearly twice that of Singaporean adults (11.1%) [4]. In Malaysia, the overall prevalence of childhood AD is 13.4%, and it is most common in Malays, males, children aged \ 2 years, and those with an atopic background, such as asthma, hay fever, and family history of atopic diseases [5]. A study using Korean national statistics gathered from health insurance data reported that the prevalence of AD in 2008 ranged from 26.5% in 12-to 23-month-old infants to 2.4% in 18 year olds [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among 13- to 14-year-old adolescents in the International Study of Asthma and Allergies in Childhood (ISAAC) Phase 3, AD prevalence for Africa and Latin America was high at 12–14% and 6–10%, respectively, whereas for Asian-Pacific countries, the Eastern Mediterranean region, and the Indian subcontinent values were lower at 3–6%; among 6- to 7-year-old children, AD prevalence for Asian-Pacific countries, Africa, and Latin America was high at approximately 10%, whereas values for the Eastern Mediterranean region and Indian subcontinent were lower at 3–5% [8]. Likewise, prevalence in the first 2 years of life was also high at 7–27% in Asian-Pacific countries, including South Korea [9], China [10], Singapore [11], Malaysia [12], and Taiwan [1315]. This review presents the diagnosis, treatment, and management of AD in developing countries in Asia, Africa, Latin America, and the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…EASI and SCORAD are established as the best instruments for evaluation of AD severity based on clinical signs with good reliability [13,14]. SCORAD has sensitivity of 65% and specificity of 64% while objective SCORAD has sensitivity of 55% and specificity of 79% [15,16]. In this study, the mean SCORAD score at baseline was 43.90 in the treatment group (severe AD) and 35.23 in the control group (moderate AD).…”
Section: Discussionmentioning
confidence: 72%